PERAN MASYARAKAT TERHADAP PEMBAYARAN RETRIBUSI SAMPAH DI KOTA SAMARINDA - Abd Rachim AF, (Universitas Widya Gama Mahakam Samarinda, 2016)
One of the environmental problems in urban areas is the pollution caused by garbage. The waste problem is caused by various factors such as population growth, living standards changes, lifestyles and behavior, as well as how the waste management system. This study aims to determine how the role of society to levy payments garbage in Samarinda. This research was descriptive; where the data is collected then compiled, described and analyzed used relative frequency analysis. The participation of the public to pay a